Familial aggregation of Parkinson’s disease and coaggregation with neuropsychiatric diseases: a population-based cohort study - Liu FC; Lin HT; Kuo C; MY Hsieh; See L; Yu HP (Clinical Epidemiology, 2018)
Fu-Chao Liu,1,2,* Huan-Tang Lin,1,2,* Chang-Fu Kuo,2–4 Mei-Yun Hsieh,4 Lai-Chu See,3,5,6 Huang-Ping Yu1,2,7 1Department of Anesthesiology, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 2College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Division of Rheumatology, Allergy and Immunology, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 4Office for Big Data Research, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 5Department of Public Health, College of Medicine, Chang Gung University, Taoyuan, Taiwan; 6Biostatistics Core Laboratory, Molecular Medicine Research Center, Chang Gung University, Taoyuan, Taiwan; 7Department of Anesthesiology, Xiamen Changgung Hospital, Xiamen, China *These authors contributed equally to this work Background: Individuals with a family history of Parkinson’s disease (PD) appear to have a higher risk of developing PD and other neuropsychiatric diseases. However, estimates of the relative risks (RRs) of PD and the roles of genetic and environmental factors in PD susceptibility are unclear. The aim of this study was to examine familial aggregation and genetic contributions to PD and the RRs of other neuropsychiatric diseases in relatives of PD patients. Methods: In this population-based family cohort study, the records of all individuals actively registered in the Taiwan National Health Insurance Research Database in 2015 were queried (N=24,349,599). In total, 149,187 individuals with a PD-affected parent, 3,698 with an affected offspring, 3,495 with an affected sibling, and 15 with an affected twin were identified. Diagnoses of PD were ascertained between January 1, 1999, and December 31, 2015. The prevalence and RRs of PD and other neuropsychiatric diseases in individuals with first-degree relatives with PD, as well as the contributions of heritability and environmental factors to PD susceptibility were investigated. Results: The prevalence of PD was 0.46% in the general population and 0.52% in individuals with first-degree relatives with PD. The RR (95% CI) for PD was 2.20 (1.41–3.45) for siblings, 1.59 (1.47–1.73) for parents, 1.86 (1.63–2.11) for offspring, 63.12 (16.45–242.16) for twins, and 1.46 (1.41–1.52) for spouses. The RR (95% CI) in individuals with first-degree relatives with PD was 1.66 (1.57–1.76) for essential tremor, 1.68 (1.61–1.75) for schizophrenia, and 1.20 (1.12–1.28) for Alzheimer’s disease. The estimated contribution to the phenotypic variance of PD was 11.0% for heritability, 9.1% for shared environmental factors, and 79.9% for non-shared environmental factors. Conclusion: First-degree relatives of PD patients are more likely to develop PD and other neuropsychiatric diseases. Environmental factors account for a high proportion of the phenotypic variance of PD. Keywords: Parkinson’s disease, familial risk, population-based family study